2006
DOI: 10.1021/om0604122
|View full text |Cite
|
Sign up to set email alerts
|

Reaction Scope and Mechanism of Sterically Induced Ruthenium-Mediated Intramolecular Coupling ofo-Carboranyl with Cyclopentadienyl. Synthesis and Structure of Ruthenium Complexes Incorporating Doubly Linked Cyclopentadienyl−Carboranyl Ligands

Abstract: Reactions of [Me(R1)A(C5H3R2)(C2B10H10)]Li2 (A = C, Si; R1 = H, Me; R2 = H, Me) with 1 equiv of RuCl2(PPh3)3 in THF afforded the corresponding doubly linked cyclopentadienyl−carboranyl ruthenium(II) hydride complexes [η 5-Me2C(C5H3)(C2B10H10)]RuH(PPh3)2 (6), [η 5-MeHC(C5H3)(C2B10H10)]RuH(PPh3)2 (7), [η 5-Me2C(5-Me-C5H2)(C2B10H10)]RuH(PPh3)2 (8), [η 5-Me2C(3/4-Me-C5H2)(C2B10H10)]RuH(PPh3)2 (9a/9b), and [η 5-Me2Si(C5H3)(C2B10H10)]RuH(PPh3)2 (10) in 72−85% isolated yields. On the other hand, interaction of [Me2C(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…30 Different ligands significantly affect the coordination configuration of the iron center, and thus influence the activation of dinitrogen. Although the simple combination of cyclopentadienyl ligands and phosphine ligands was used in several dinitrogen complexes, [38][39][40][41][42][43][44][45] studies on iron-dinitrogen complexes bearing cyclopentadienylphosphine ligands, for example L in Scheme 1, in which the two commonly used strong coordination moieties of different steric and electronic properties are linked together, are few due to the formation of stable sandwich-type ferrocene structures. [46][47][48] We have previously developed a convenient synthetic method for cyclopentadienyl-phosphine ligands (L).…”
Section: Introductionmentioning
confidence: 99%
“…30 Different ligands significantly affect the coordination configuration of the iron center, and thus influence the activation of dinitrogen. Although the simple combination of cyclopentadienyl ligands and phosphine ligands was used in several dinitrogen complexes, [38][39][40][41][42][43][44][45] studies on iron-dinitrogen complexes bearing cyclopentadienylphosphine ligands, for example L in Scheme 1, in which the two commonly used strong coordination moieties of different steric and electronic properties are linked together, are few due to the formation of stable sandwich-type ferrocene structures. [46][47][48] We have previously developed a convenient synthetic method for cyclopentadienyl-phosphine ligands (L).…”
Section: Introductionmentioning
confidence: 99%
“…96 In 2006, the same authors published an extension of this work in-which a series of cyclopentadienyl-carboranyl halfsandwich complexes of ruthenium was synthesised following the same strategy. 97 Based on different examples, they showed that the coupling reaction of the Cp ring with the dicarbacloso-dodecarborane derivative requires the absence of a substituent on one of the carbon atoms of the cyclopentadienyl unit. Moreover, the presence of a triphenylphosphine coordinated to the metal atom is essential, which indicates a mechanism based on sterically-induced coupling.…”
Section: C Functionalised Ortho-dicarba-closo-dodecarborane Ligandmentioning
confidence: 99%
“…Treatment of the dilithium salts of [Me 2 C(C 5 H 4 )(C 2 B 10 H 10 )] 2− with [RuCl 2 (COD)] x at room temperature affords the constrained-geometry ruthenium carboranyl complexes [η 5 :σ-Me 2 C(C 5 H 4 )(C 2 B 10 H 10 )]Ru(COD) [48] . On the other hand, interaction between Li 2 [Me 2 C(C 5 H 4 )(C 2 B 10 H 10 )] and RuCl 2 (PPh 3 ) 3 in a 1 : 1 molar ratio at room temperature gives a ruthenium(Ⅱ ) hydride complex [η 5 -C 5 H 3 {Me 2 C(C 2 B 10 H 10 )}]RuH(PPh 3 ) 2 (27) bearing a new ligand formed by a C cage -C ring coupling (Scheme 11) [49,57] . This result is unexpected and very different from literature work [55,56] .…”
Section: Steric Hindrance-induced C Cage -C Coupling Reactionmentioning
confidence: 99%